Lamproite dykes in the Napier Complex at Tonagh Island, Enderby Land, East Antarctica - Miyamoto, Tomoharu; Grew, Edward S.; Sheraton, John W.; Yates, Martin G.; Dunkley, Daniel J.; Carson, Christopher J.; Yoshimura, Yasutaka; Motoyoshi, Yoichi (National Institute of Polar Research, 2000)
P(論文) Lamproite dykes, discovered during JARE-40, form NS-trendmg, subvertical sheets over a 2 km distance in southeastern Tonagh Island They range from a few centimeters to one meter in thickness and up to several meters in length The lamproite is holocrystalline and consists dominantly of ferrian microcline, potassic nchterite, biotite and apatite, trace amounts of quartz are often present Grain size is generally 0 1 to 3 mm The lamproite is noteworthy for its very high contents of K_2O (9 33-11 66 wt%), P_2O_5 (2 66-4 21 wt%), Be (7-19ppm), F (077-1 44 wt%), Rb (253-479 ppm), Sr (2331-3306 ppm), Zr (1310-2400 ppm), Nb (889-209 ppm), Ba (931-12992 ppm), light REE, Th (13-145 ppm) and U (8-16 ppm), and relatively low Al_2O_3 (7 66-10 15 wt%) and Na_2O (1 03-1 95 wt%) Rb-Sr internal isochrons define ages of 466 ±4 Ma and 476 ±6 Ma and initial ratios of 0 70949 ±000010 and 070966 ±000010, respectively The small difference in age between the two samples might be related to minor alteration following original crystallization Lamproites at all three localities have intruded areas where the Archean Napier Complex was reactivated 500 Ma ago by pegmatite activity and by superimposed amphibohte-facies metamorphism and deformation Overall, the temporal and spatial relationships between lamproite intrusion and zones of late-Proterozoic to Cambrian reactivation of the Napier Complex are similar to those between ultrapotassic igneous activity and Pan African deformation and metamorphism in Eastern Queen Maud Land This suggests that the effects of the amalgamation of east and west Gondwana extended eastward in Antarctica from Queen Maud Land to Enderby Land departmental bulletin paper